Does a two-year period of orthokeratology lead to changes in the endothelial morphology of children?. Issue 2 (April 2018) - Cheung, Sin Wan; Cho, Pauline
Highlights: Orthokeratology did not affect the changes in endothelial cell morphology in children aged 6–12 years. Endothelial cell density reduced by 98 cells/mm 2 in ortho-k subjects and 56 cells/mm 2 in control subjects in two years. Mild pleomorphism was observed in the both central and superior corneal locations. Mild polymegathism was observed only in the central cornea. Abstract: Purpose: To compare changes in endothelial morphology in the central and superior cornea in subjects wearing single-vision spectacles and orthokeratology lenses over two years. Methods: Endothelial images of the two locations of 99 subjects (6–12 years) from completed myopia control studies were analysed. Endothelial cell density (ECD), coefficient of variation in cell size (CV), and hexagonality (HEX) before and two years after treatment were compared between the two groups of subjects. Results: Baseline ECD and CV in the central cornea were slightly lower than those in the superior cornea, but no significant difference in HEX was found in the two corneal locations. After two years, reduction in ECD and increase in CV were only significant in the central cornea, but not in the superior cornea. Reduction in HEX was significant in both corneal locations. Subjects receiving orthokeratology had smaller reduction in ECD in the central cornea compared to the controls (orthokeratology: 56 ± 94 cells/mm 2 ; control: 98 ± 91 cells/mm 2, p = 0.024), otherwise, there were no significant differences in the changes in endothelial morphology in the two corneal locations between the two groups of subjects. Conclusions: The current study confirmed that there were differences in endothelial morphology of central and superior cornea of Chinese children aged 6–12 years. The morphological response to normal ageing differed between the two corneal locations as reduction in cell density and polymegathism were found only in the central cornea whilst pleomorphism was found in both locations. Orthokeratology lens wear had minimal effect on the developmental changes in endothelial morphology.